Depression, substance abuse and stigma among men who have sex with men in coastal Kenya. (December 2015) - Secor, Andrew M.; Wahome, Elizabeth; Micheni, Murugi; Rao, Deepa; Simoni, Jane M.; Sanders, Eduard J.; Graham, Susan M.
Abstract : Objectives: Mental health conditions can erode quality of life and interfere with health-related behaviours such as medication adherence. We aimed to determine the prevalence and correlates of depression and other psychosocial factors among self-identified men who have sex with men (MSM) in coastal Kenya. Design: A cross-sectional survey. Methods: Psychosocial and mental health characteristics were assessed in an audio computer-assisted self-interview (ACASI) survey among 112 MSM participating in two ongoing HIV-positive and HIV-negative cohorts in Mtwapa, Kenya. Results: One-third of participants met criteria for major depressive disorder [16.1%, 95% confidence interval (95% CI) 9.8–24.2] or other depressive disorder (15.2%, 95% CI 9.1–23.2). Alcohol abuse was reported by 45% of respondents (95% CI 35.2–54.3) and other substance abuse by 59.8% (95% CI 50.1–69.0). Sexual and HIV stigma were moderate, with median scores of 11 [interquartile range (IQR) 6–17, potential range 0–33] and 25 (IQR 23–29, potential range 11–44), respectively. There were significant bivariate correlations between alcohol abuse, other substance abuse, sexual stigma and childhood and recent abuse. In a multivariable linear regression model, sexual stigma (beta = 0.17, 95% CI 0.03–0.32) and marriage to a woman (beta = -2.41 95% CI -4.74 to -0.09) were each associated with depression score. Conclusion: We found moderate to high levels of depression and substance abuse, and moderate levels of sexual stigma. These variables were highly inter-correlated and associated with an experience of trauma or abuse. Comprehensive mental health services are needed in this population to address these issues.